1979
DOI: 10.1007/bf00122045
|View full text |Cite
|
Sign up to set email alerts
|

Adh system and genetic background: Interaction with wing length in Drosophila melanogaster

Abstract: in order to test the adaptive value of Adh genotypes in connection with the genetic background, we crossed two unrelated strains of Drosophila melanogaster, Canton and Oregon; the former, homozygous for AdhS, exhibited shorter wing length and higher reproductive fitness, the latter, homozygous for AdhF, exhibited longer wing length and lower reproductive fitness in standard conditions of rearing.The F2 progenies appear to be in equilibrium at the enzyme locus; nevertheless the Adh genotypes are not randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1980
1980
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…In two previous papers we suggested that the apparent selective responses at the Adh locus in Drosophila melanogaster are not independent either of the genetic background or of variation at the gene pool level brought about by changes of selection pressure (Pieragostini et al, 1979(Pieragostini et al, , 1981. Moreover notwithstanding different environmental temperatures and at variance with the findings of other authors (Pipkin et al, 1973;Johnson & Powell, 1974;Vigue & Johnson, 1973), we found that the Adh locus was not the target of selection.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In two previous papers we suggested that the apparent selective responses at the Adh locus in Drosophila melanogaster are not independent either of the genetic background or of variation at the gene pool level brought about by changes of selection pressure (Pieragostini et al, 1979(Pieragostini et al, , 1981. Moreover notwithstanding different environmental temperatures and at variance with the findings of other authors (Pipkin et al, 1973;Johnson & Powell, 1974;Vigue & Johnson, 1973), we found that the Adh locus was not the target of selection.…”
Section: Introductioncontrasting
confidence: 56%
“…After the oviposition period, the 120 mothers were assayed for five quantitative characters (wing length and width, thorax length and width and head width) and for Adh genotype following the procedure detailed in Pieragostini et al, 1979. These 120 groups of data (5 metric traits and Adh genotype × each female) represent the last sample of the original population, to which we will refer as 30M.…”
Section: Methodsmentioning
confidence: 99%
“…(1) The present data refer to a cage population of Drosophila melanogaster obtained by crossing Canton strain 99 and Oregon strain ~(~ (see Pieragostini et al,, 1979 for details) and kept at 25 °C. Seventy QQ and 70 6'~ of the F l generation from the above cross were placed in a 15 × 20 × 30 em polymethylmetalcrylate box, having six holes in two rows on the two largest sides, where vials containing the culture media may be placed.…”
Section: Methodsmentioning
confidence: 99%
“…From the emerging progeny of the sample pairs, 100 virgin 9Q were taken and wing length and width, thorax length and width and head width, were measured (F_, wing length measures have already been reported in Pieragostini et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation